Application of the automated system for sample preparation for determination of polycyclic aromatic hydrocarbons by chromato-mass-spectrometry - E A Belinskaya; G V Zykova; S Yu , Semenov; G G Finakov (RUDN Journal of Ecology and Life Safety, 2012)
The technique of the analysis of polycyclic aromatic hydrocarbons in soils with application of the high-speed automated system of sample preparation is developed. Advantages of the automated system before standard sample preparation are revealed.